MODIFICATION NATURAL ZEOLIT BY PLANTING INHIBITOR OF Cu WITH BATCH METHOD AS RAW MATERIAL FOR ANTISEPTIC MEDICINE - Fatimah, Dewi (Jurnal Zeolit Indonesia, 2009)
Natural zeolite can be develop as alternative raw materials pharmaceutical product, particularly as an absorbent of microbial pathogens and it is widely spread in almost province at Indonesia. The study conducted by modifying natural zeolite by planting inhibitor of Cu which functions as raw materials for medicine, especially as an antiseptic carrier. Process of planting Cu was conducted on Zeolite-H with variation stirring time of 2,4 6, and 8 hours at room temperature. Inhibitor planting process by batch methods was conducted on batch reactor. The result showed that purification process could be reduce a free oxides from Si, Al, Ti, Ca, and Fe which covered crystal structure and there is not occurred a peaks degradation of modernite and clinoptilolite on XRD diffractogram. Through SEM analysis can be seen form of modernite and clinoptilolite crystal that result of purification process more clearer. The EDX analysis showed that conversion to zeolite-Cu was successfully done and highest absorption of ASS at stirring time of 6 hours with concentration Cu of 299,5 ppm. Dynamic oligo antiseptic carrier test from zeolite-Cu was conducted on Candida albicans and Escherichia coli Growth. The media used were gel nutrient on various concentrations at incubation time of 30oC for 24-48 hours. The result showed that Zeolite-Cu can significantly reduce a Candida albicans and Escherichia coli growth.